Research Progress on Preparation and Electrocatalytic Performance of Tin Dioxide Nanomaterials - Liu, Chang; Wang, Weixia; Wu, Feiyang; Zhang, Jiayi; Chen, Chunguang; Cheng, Ping; Zhu, Yuanzheng; Zhang, Shuping; Seong, Gimyeong (Chemical record, 2025)
In the contemporary era of rapid economic growth, addressing the energy issue constitutes a significant subject. In contrast to traditional fossil energy, fuel cells, through specific transformation routes, can generate more energy and reduce pollution under the same conversion relationship. Direct alcohol fuel cells, as a type of proton exchange membrane fuel cell, exhibit relatively superior performance. During the process of converting chemical energy into electrical energy, the conversion efficiency of the electrode is a crucial aspect of the fuel cell′s performance, thereby giving rise to electrode electrocatalysis. Nevertheless, the noble metal catalysts employed in current direct alcohol fuel cells are confronted with issues such as high cost, susceptibility to poisoning, and poor durability. A new approach to these problems is urgently needed. Loading noble metals onto metal oxides has been verified as an effective means. Among them, tin dioxide has attracted the attention of researchers due to its outstanding stability, anti‐toxicity, and its positive auxiliary role in electrocatalysis. This article will conduct a review of the research progress in loading noble metals on tin dioxide carriers for the electrocatalytic oxidation of small molecule alcohols from various microstructures and loading methods. Finally, the research on metal dioxide electrocatalysts is prospected. Direct alcohol fuel cells have excellent performance, but the noble metal catalyst of their electrode has the problems of high cost, easy poisoning and poor durability. Tin dioxide can play an active auxiliary role in the catalytic process. In this paper, the study of supporting noble metals on tin dioxide support for electrocatalysis of small molecular alcohols is reviewed in terms of different micro‐structure and loading methods.